2009
DOI: 10.1016/j.neurobiolaging.2007.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin level and cognition in the elderly: Findings from the Health ABC Study

Abstract: Leptin is a peptide hormone secreted by adipocytes. It has been shown to modulate production and clearance of amyloid beta (Aβ) in rodent models. We sought to determine if serum leptin was associated with cognitive decline in the elderly.We studied 2871 well-functioning elders, aged 70-79, who were enrolled in a prospective study. Serum leptin concentrations were measured at baseline and analyzed by mean ± 1 SD. Clinically significantly cognitive decline over 4 years was defined as ≥ 5 point drop on the Modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
146
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(161 citation statements)
references
References 58 publications
14
146
1
Order By: Relevance
“…The authors found that 25% of subjects developed AD in the lowest quartile of leptin as compared to 6% in the highest quartile, and circulating leptin levels correlated with gray matter volume in the brain, specifically in the hippocampus. Further, in another study by Holden et al [47], significantly less likelihood of cognitive decline was observed in elders from the high serum leptin group. However, no correlation between serum leptin levels and cognitive decline in PwAD has been reported either [48].…”
Section: Discussionmentioning
confidence: 89%
“…The authors found that 25% of subjects developed AD in the lowest quartile of leptin as compared to 6% in the highest quartile, and circulating leptin levels correlated with gray matter volume in the brain, specifically in the hippocampus. Further, in another study by Holden et al [47], significantly less likelihood of cognitive decline was observed in elders from the high serum leptin group. However, no correlation between serum leptin levels and cognitive decline in PwAD has been reported either [48].…”
Section: Discussionmentioning
confidence: 89%
“…Jak-Stat, Erk, PI3K/Akt and AMPK [138,139] Leptin is known to affect satiety, food intake and body weight through its action in hypothalamus, but the hormone has more diverse neurotrophic and neuroprotective actions in the brain and also affects hippocampal neurigenesis and long-term potentiation [138,139,140]. Several case-control and large population based prospective studies have shown an inverse association of circulating leptin levels with AD or general cognitive decline [141,142,143]. In case of adiponectin the epidemiological link with AD risk is less clear.…”
Section: Adipokinesmentioning
confidence: 99%
“…Despite extensive animal research on leptin, there are limited studies in human populations. A subgroup of the Framingham cohort and the Health ABC Study have demonstrated that higher leptin levels were associated with lower dementia risk and higher brain volume 7,7 or 4 years after leptin was assayed, respectively (Lieb et al 2009;Holden et al 2009). On the other hand, Rajagopalan et al (2013) reported that elderly with higher leptin levels (obese) showed concomitant greater global brain atrophy, highlighting the deleterious effect of central leptin insufficiency associated with obesity.…”
Section: Leptinmentioning
confidence: 99%